2017
DOI: 10.1080/10826084.2017.1334066
|View full text |Cite
|
Sign up to set email alerts
|

Causal Factors of Increased Smoking in ADHD: A Systematic Review

Abstract: Smoking is probably best explained by a combination of imitation, peer pressure and typical traits of ADHD. In contrast, the positive relation between ADHD and nicotine dependence is currently best explained by the self-medication hypothesis. This hypothesis has a clear pharmacological rationale and is supported by ample evidence, but awaits confirmation from longitudinal naturalistic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 125 publications
(144 reference statements)
7
59
0
Order By: Relevance
“…While previous observational studies may have been biased by (unmeasured) confounding, our approach of using genetic variants as instrumental variables is more robust to confounding and reverse causality. We were not able to identify the exact mechanism of causation, but it seems plausible that higher levels of impulsivity may lead individuals with ADHD liability to try out cigarettes or cannabis without considering their possible negative consequences 5,49 . Another potential mechanism is 'selfmedication', whereby a substance is used because of its (real or perceived) positive effects on ADHD symptomatology -even though such effects might not actually exist 50 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…While previous observational studies may have been biased by (unmeasured) confounding, our approach of using genetic variants as instrumental variables is more robust to confounding and reverse causality. We were not able to identify the exact mechanism of causation, but it seems plausible that higher levels of impulsivity may lead individuals with ADHD liability to try out cigarettes or cannabis without considering their possible negative consequences 5,49 . Another potential mechanism is 'selfmedication', whereby a substance is used because of its (real or perceived) positive effects on ADHD symptomatology -even though such effects might not actually exist 50 .…”
Section: Discussionmentioning
confidence: 96%
“…There is extensive research showing that genetic influences on smoking initiation are mediated via impulsivity-related traits 5 . This was confirmed by our findings that the genetic instrument for smoking initiation also showed strong evidence for a causal effect on ADHD symptoms in children <13 years (who would not yet have started smoking).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have established the clinical relevance of ADHD symptoms (impulsivity, disinhibition, executive function deficits, and slowed mental processing) for the prediction of SUD development and persistence [19, 20]. These studies suggested that treatment outcomes for SUD may be improved by early and accurate identification and targeting ADHD symptoms in this population.…”
Section: Introductionmentioning
confidence: 99%